Qualitative Team Formation Analysis in Football: A Case Study of the 2018 FIFA World Cup - Beernaerts, Jasper; De Baets, Bernard; Lenoir, Matthieu; Van de Weghe, Nico (Frontiers in Psychology, 2022)
In this paper, we explore the use of the Static Qualitative Trajectory Calculus (QTCS), a qualitative spatiotemporal method based on the Qualitative Trajectory Calculus (QTC), for the analysis of team formations in football. While methods for team formation analysis in sports are predominantly quantitative in nature, QTCS enables the comparison of team formations by describing the relative positions between players in a qualitative manner, which is more related to the way players position themselves on the field. QTCS has the potential to allow to monitor to what extent a football team plays according to a coach’s predetermined formation. When applied to multiple matches of one team, the method can contribute to the definition of the playing style of a team. We present an experiment aimed at identifying the team formation played by Belgian national football team during the 2018 FIFA World Cup held in France.